Development and evaluation of the extended learning unit model for online course construction in UNIMAS - Goh, Kok Luong (2003)
E-learning is becoming widely adopted as a means of teaching-learning in many educational institutions. A course authoring system plays an important role in the development of course contents for an E-learning system. Current authoring systems are facing a number of problems in providing flexible authoring capability to enable the sharing and reusability of learning content.